Weight gain and neuroadaptations elicited by high fat diet depend on fatty acid composition. (April 2021) - Adermark, Louise; Gutierrez, Saray; Lagström, Oona; Hammarlund, Maria; Licheri, Valentina; Johansson, Maria E.
Abstract: Overconsumption of food is a major health concern in the western world. Palatable food has been shown to alter the activity of neural circuits, and obesity has been linked to alterations in the connectivity between the hypothalamus and cortical regions involved in decision-making and reward processing, putatively modulating the incentive value of food. Outlining neurophysiological adaptations induced by dietary intake of high fat diets (HFD) is thus valuable to establish how the diet by itself may promote overeating. To this end, C57BL/6 mice were fed HFD rich in either saturated fatty acids (HFD-S) or polyunsaturated fatty acids (HFD-P), or a low-fat control diet (LFD) for four weeks. Food and energy intake were monitored and ex vivo electrophysiology was employed to assess neuroadaptations in lateral hypothalamus (LH) and corticostriatal circuits, previously associated with food intake. In addition, the effects of dietary saturated and polyunsaturated fatty acids on the gene expression of NMDA, AMPA and GABAA receptor subunits in the hypothalamus were investigated. Our data shows that mice fed HFD-P had increased daily food and energy intake compared with mice fed HFD-S or LFD. However, this increase in energy intake had no obesogenic effects. Electrophysiological recordings demonstrated that HFD-P had a selective effect on glutamatergic neurotransmission in the LH, which was concomitant with a change in mRNA expression of AMPA receptor subtypes Gria1, Gria3 and Gria4, with no effect on the mRNA expression of NMDA receptor subtypes or GABAA receptor subtypes. Furthermore, while synaptic output from corticostriatal subregions was not significantly modulated by diet, synaptic plasticity in the form of long-term depression (LTD) was impaired in the dorsomedial striatum of mice fed HFD-S. In conclusion, this study suggests that the composition of fatty acids in the diet not only affects weight gain, but may also modulate neuronal function and plasticity in brain regions involved in food intake. Graphical Abstract: ga1 Highlights: Fatty acid content affects weight gain. HFD up-regulates AMPA receptor signaling in LH. Intake of saturated fatty acids impairs synaptic plasticity. Effects by HFD is brain region specific. HFD-P primarily affects glutamatergic signaling.